International Practice of Provision of Guarantees for Implementation of Investment Projects - KOSOV, Mikhail Evgenievich; SIGAREV, Aleksandr Victorovich; POPKOV, Sergey Yuryevich; EKIMOVA, Ksenia Valerievna; FEDOTOV, Alexander Mikhailovich (Journal of Advanced Research in Law and Economics, 2020)
Subject. State support for the country's economy, especially the support for its high-tech sector, is of great importance during a crisis. State guarantees are also one of the key instruments of state support for investment activity in Russia. Significant successful practice of using this instrument has been accumulated in Canada, Spain, the Netherlands, the USA, Turkey, Sweden, and Chile. The world experience indicates that the implementation of projects as public-private partnerships (PPP) leads to the completion of the project on time and in accordance with its budget more often than when implementing the project based on public funding only. Goals. The study is aimed at analysis of the mechanism of state guarantees in foreign countries, the conditions and consequences of their provision. Methods. The research methods include a review of the scientific literature in this area, synthesis and analysis of the information obtained, as well as comparison, formalization, and specification. Results. The practical implementation of state guarantees in foreign countries has been analyzed in the study. The specifics and the possibility of applying the best practices in Russia have been revealed. Conclusion. The fiscal legislation of Russia includes a developed system for regulating the provision of guarantees and establishes the requirements for the application and accounting of state guarantees that are very conservative in accordance with international standards. The application of the world practice in the creation of guarantee agencies in order to support small and medium-sized enterprises can have a positive effect on business activities. The need to diversify directions for the provision of state guarantees with a view to balanced economic development must also be noted.